Analisis Panel Regression: Profitability, Debt Policy and Economic Value Added to the Value of Automotive and Component Companies in Indonesia - Nababan, Meli Julianty Permatasari; Hutabarat, Francis; Malau, Harman (International Journal of Business, Law, and Education, 2024)
This study aims to prove the effect of profitability (Return On Equity), Debt Policy (Debt to Equity Ratio), and Economic Value Added on Company Value (Price Book Value), both partially and simultaneously. This research approach is quantitative which is associative in nature to prove the effect of independent variables on dependent variables. The population of this study is an automotive company listed on the IDX using 12 sample companies during the 2019 - 2022 observation period so that 48 observation data units are obtained. The data analysis method used is Panel Regression which uses cross-sectional and time series data. The methods used are Chow Test, Hausman Test to estimate the selected regression model. This study proves that the Fixed Effect Model is the selected regression model. The results prove that Profitability as measured by ROE has no significant effect on the value of Automotive companies on the IDX Debt policy as measured by DER has a significant effect on the value of Automotive companies on the IDX. Economic Value Added (EVA) has a significant effect on the value of Automotive companies on the IDX. The results of simultaneous testing prove that profitability, debt policy and EVA together have an effect on firm value.